Hypertriglyceridemia—Causes, Significance, and Approaches to Therapy - Santos-Baez, Leinys S.; Ginsberg, Henry N. (Frontiers in Endocrinology, 2020)
Hypertriglyceridemia (HTG) is a common metabolic disorder with both genetic and lifestyle factors playing significant roles in its pathophysiology. HTG poses a risk for the development of cardiovascular disease (CVD) in the population at large and for pancreatitis in about two percent of individuals with extremely high levels of triglycerides (TG). This manuscript summarizes the mechanisms underlying the development of HTG as well as its management, including emerging therapies targeted at specific molecular pathways.